Spatial Overlap and Habitat Selection of Corvid Species in European Cities - Abou Zeid Farah; Morelli Federico; Ibáñez-Álamo Juan Diego; Díaz Mario; Reif Jiri; Jokimäki Jukka; Suhonen Jukka; Kaisanlahti-Jokimäki Marja-Liisa; Markó Gabor; Bussière Raphael; Mägi Marko; Tryjanowski Piotr; et al. (MDPI, 2023)
Understanding habitat and spatial overlap in sympatric species of urban areas would aid in predicting species and community modifications in response to global change. Habitat overlap has been widely investigated for specialist species but neglected for generalists living in urban settings. Many corvid species are generalists and are adapted to urban areas. This work aimed to determine the urban habitat requirements and spatial overlap of five corvid species in sixteen European cities during the breeding season. All five studied corvid species had high overlap in their habitat selection while still having particular tendencies. We found three species, the Carrion/Hooded Crow, Rook, and Eurasian Magpie, selected open habitats. The Western Jackdaw avoided areas with bare soil cover, and the Eurasian Jay chose more forested areas. The species with similar habitat selection also had congruent spatial distributions. Our results indicate that although the corvids had some tendencies regarding habitat selection, as generalists, they still tolerated a wide range of urban habitats, which resulted in high overlap in their habitat niches and spatial distributions.